PM2.5 자동측정장비 비교 및 정도관리 방안 - 박미경(Mikyung Park); 박진수(Jin Su Park); 조미라(Mira Jo); 이용환(Yong Hwan Lee); 김현재(Hyun Jae Kim); 오준(Jun Oh); 최진수(Jin Soo Choi); 안준영(Joon Young Ahn); 홍유덕(You Deog Hong) (한국대기환경학회지(국문), 2017)
Measurements using five real-time particle samplers were compared to measurements using three NRM (National Reference Method system) filter-based samplers (Gravimetric method) at Incheon, Korea, between May and August, 2014. The purpose of this study was to suggest the quality assurance/quality control (QA/QC) method of each instrument for use in a real-time continuous particle sampler to measure the mass of airborne particles with an aerodynamic diameter less than 2.5 μm (PM2.5). Five real-time particle samplers of BAM1020, FH62C_14, TEOM, PM-711 and SPM-613 were evaluated by comparing its measured 23 hr average PM2.5 concentrations with those measured with NRM filter-based samplers simultaneously. The parameters (e.g. Inlet heating condition, Slope factor, Film response, Intercept, Background, Span value) of the real-time samplers were optimized respectively by conducting test performance evaluation during 7 days in field sampling. For example, inlet heating temperature of TEOM sampler controls 35~40℃ to minimize the fluctuation of the real-time measurement data and background value of BAM1020 is the key factor affecting the accuracy of PM2.5 mass concentration. We classified the PM2.5 concentration according to relative humidity (80%) to identify water absorbed in aerosols by measuring the β-ray samplers (BAM1020, FH62C_14) and TEOM. β-ray samplers were not strongly affected by relative humidity that the difference of the average PM2.5 concentration was about 5%. On the other hand, The TEOM sampler overestimated PM2.5 mass concentration about 15% at low relative humidity (<80%). KCI Citation Count: 0